The Development of Cognitive Strategies Based on Sufficiency Economy Philosophy Approach for Enhancing Contextual Quality of Life of Older Adults in Upper Northern Thailand - Jaksomsak, Kaweewat; Malakul Na Ayudhya, Prasarn; Kirdpitak, Pongpan (Journal of Behavioral Science for Development, 2023)
This research is mixed method research. The purposes of this research were to 1) study the contextual quality of life of older adults in upper northern Thailand, 2) develop the cognitive strategies based on the sufficiency economy philosophy approach, and 3) study the effect of the cognitive strategies based on sufficiency economy philosophy approach for enhancing contextual quality of life of older adults in upper northern Thailand. The sample size of this study is 204 older adults whose living in Chiang Rai, and Chiang Mai province to study the contextual quality of life and 40 older adults from Chiang rai province whose contextual quality of life scale were lower than 25 percentiles. They were randomly assigned to experimental group and control group. Each group consisted of 20 older adults. The research instrument comprised of 1) the cognitive strategies based on sufficiency economy philosophy approach and 2) the contextual quality of life scale measuring. The results of this study were: 1) 204 older adults were at high level of quality of life with an average score of 122.7 scores (122.7 ± 16.24), 2) the cognitive strategies based on sufficiency economy philosophy approach was developed by theoretical concepts related to risk management, self-management, knowledge management, and action learning, and 3) the contextual quality of life of experimental group at posttest and follow-up were significantly higher than pretest at the .01 level (F = 92.84, p = 0.01) also higher than control group at the .01 level (F = 59.78, p = 0.01)